ORNAMENTAL ART IN UZBEK ARCHITECTURE: TILEWORK, PATTERNS, MUQARNAS, AND GANCH CARVING STYLES - A. R. Abobakirov (Ecominds Press, 2025)
Ornamental art in Uzbek architecture represents one of the most profound and enduring achievements of Islamic civilization in Central Asia, manifesting the synthesis of spirituality, craftsmanship, and aesthetic refinement. This study examines the four principal styles of decorative art—tilework (koshinkorlik), patterns (naqsh), muqarnas, and ganch carving—through their historical development, stylistic characteristics, and cultural significance within the broader architectural heritage of Uzbekistan. Drawing on historical sources, architectural surveys, and comparative stylistic analysis, the paper situates Uzbek ornamental art within the trajectory of Islamic art from the Timurid period through the Khanates, highlighting the technical innovations, symbolic meanings, and regional schools of craftsmanship that contributed to its global reputation. Results demonstrate that tilework in monuments such as the Registan and the Kalon Mosque served as monumental expressions of faith and dynastic power, while geometric and vegetal patterns provided both visual harmony and metaphysical symbolism. Muqarnas, employed in domes, iwans, and portals, created transitions between structural elements while embodying cosmological order, and ganch carving transformed architectural interiors into luminous spaces filled with intricate ornamentation. Discussion emphasizes that Uzbek ornamental art was not static but dynamically integrated influences from Persia, India, and the wider Islamic world, while preserving a distinctive regional identity. The conclusion underscores the enduring relevance of these traditions for contemporary Uzbek culture and their recognition as part of world heritage, particularly through monuments inscribed on the UNESCO World Heritage List.
Keywords: Uzbek Architecture; Tilework; Patterns; Muqarnas; Ganch Carving; Islamic Ornament; Central Asian Heritage.